QRIS IMPLEMENTATION IN MSMES:A STUDY OF EASE OF USE AND ITS IMPACT ON TRANSACTION EFFICIENCY (STUDY OF MSMES IN KECAMATAN TELUK AMBON ) - Rita J D Atarwaman; Saraun kaliky; Phuput Aprilia Arif; Riyadh Gunawan (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the implementation of the Quick Response Code Indonesian Standard (QRIS) among Micro, Small, and Medium Enterprises (MSMEs) and analyzes the effect of ease of use on transaction efficiency. This research employs a quantitative explanatory approach based on a field study conducted in Teluk Ambon District. Data were collected through structured questionnaires distributed to MSME actors who have implemented QRIS as a digital payment system. A total of 30 MSMEs were selected using purposive sampling based on predefined criteria. The collected data were analyzed using validity and reliability tests, descriptive statistics, simple linear regression analysis, t-test, and coefficient of determination (R²). The results show that ease of use has a positive and significant effect on transaction efficiency, with a significance value of 0.033, which is lower than the 0.05 significance level. The coefficient of determination (R²) value of 0.153 indicates that ease of use explains 15.3% of transaction efficiency, while the remaining 84.7% is influenced by other factors not examined in this study. These findings support the Technology Acceptance Model (TAM) proposed by Davis and confirm that QRIS contributes to improving transaction efficiency among MSMEs. This study provides theoretical contributions to digital payment adoption literature and practical implications for policymakers, financial institutions, and MSME actors.